Formation of Micro- and Nano-Trenches on Epitaxial Graphene - Tingwei Hu; Xiangtai Liu; Dayan Ma; Ran Wei; Kewei Xu; Fei Ma (Applied Sciences, 2018)
Catalytic cutting by metal particles under an atmosphere environment is a promising method for patterning graphene. Here, long straight micro-trenches are produced by the sliding of metal particles (Ag and In) on epitaxial graphene (EG) substrate under the ultra-high vacuum (UHV) annealing. The morphology and orientation relationship of the micro-trenches are observed by scanning electron microscopy (SEM), and the damage effect is confirmed by Raman scattering. Atomic force microscopy (AFM) and scanning tunneling microscopy (STM) are further adopted to atomically characterize the sliding behavior of metal particles, which resembles a similar etching method and can be used to make graphene nano-trenches. The study provides us with more understanding about the mutual effects between metals on EG, which hopes to pave the way for the applications of graphene-based devices.